O homem em farrapos: a experiência da moda em Flávio de Carvalho - Rosa, Victor Da (Programa de Estudos Pós-graduados em Comunicação e Semiótica - PUC-SP, 2018)
Abstract The article analyzes in detail a set of writings by Flávio de Carvalho about fashion, first published in 1956 and then reissued in 2010, in perspective with two contemporary theorists who also dedicated themselves to look into the subject: Emanuele Coccia and Boris Groys. The central idea is to explore the figure of the “man in rags”, a figure that Flávio himself develops through a series of reflections on the history of clothing, as a contribution to the avant-garde debate around the “new man”. It enables an understanding of another central concept proposed by the author, that of Unisex , and also to revisit its celebrated performance from the creation of a new look. Thus, the article proposes to debate not only the spot occupied by fashion in the trajectory of this singular artist, but also to draw attention to the relevance and topicality of Flávio’s works regarding such debate.

Resumo O artigo analisa em detalhe um conjunto de textos de Flávio de Carvalho sobre moda, publicados em 1956 e reeditados em 2010, em perspectiva com dois teóricos contemporâneos que também se dedicaram a pensar sobre o assunto: Emanuele Coccia e Boris Groys. A ideia central é pensar a figura do “homem em farrapos”, figura que o próprio Flávio desenvolve por meio de uma série de reflexões sobre a história do vestuário, como contribuição ao debate vanguardista em torno do “homem novo”. Por meio dela, é possível compreender outro conceito central proposto pelo autor, o de Unissexo, e também revisitar a sua célebre performance realizada a partir da criação de um new look. Dessa forma, o artigo procura debater não apenas o lugar que a moda ocupou na trajetória desse artista singular, mas também chamar atenção para a pertinência e a atualidade do pensamento de Flávio a respeito de tal debate.
The man in rags: fashion experience in Flávio de Carvalho
Keywords: Flávio de Carvalho; fashion; experience; rag; Flávio de Carvalho; moda; experiência; farrapo